Lipid composition in common carp (Cyprinus carpio) sperm possessing different cryoresistance - Horokhovatskyi, Y; Sampels, S; Cosson, J; Linhart, O; Rodina, M; Fedorov, P; Blecha, M; Dzyuba, B (Cryobiology, 2016)
The present study examined the lipid composition of plasma membranes in carp sperm with different post-thaw motility. The approach adapted for carp sperm cryopreservation, which involves the selection of the most effective protocol for individual males by comparing two cryoprotective media, was applied to the cryopreservation procedure. Sperm motility prior to freezing was greater than 80% but decreased to 40% in one group and to 10% in another group following cryopreservation. Lipid content of fresh sperm in all groups was analysed by thin layer chromatography and gas chromatography, with significant differences in phospholipid content, cholesterol and free fatty acids detected between groups, whereas the cholesterol/phospholipid ratio was extremely similar between groups (0.52 ± 0.038 and 0.52 ± 0.022). Increasing concentrations of saturated fatty acids, monounsaturated acids and decreasing concentrations of polyunsaturated n-6 fatty acids were negatively correlated (P < 0.05) with post-thaw motility of the carp sperm.
Keywords: zmrazování; Male; Cholesterol; Phospholipids; uchování spermatu; Animals; kryoprotektivní látky; Carps; spermie; Carp sperm; mastné kyseliny; buněčná membrána; mužské pohlaví; cholesterol; fosfolipidy; Semen Preservation; Cryoprotective Agents; Spermatozoa; chromatografie plynová; Sperm motility; motilita spermií; kryoprezervace; Sperm Motility; Fatty Acids; zvířata; Cryopreservation; Chromatography, Thin Layer; Cell Membrane; Lipid content; chromatografie na tenké vrstvě; kapři; Cryoresistance; Freezing; Chromatography, Gas